Animal waste containment in lagoons - Reddi, Lakshmi N. (American Society of Civil Engineers, 2005)
"Animal Waste Containment in Lagoons provides a comprehensive view of the state-of-the-art practice of animal waste containment and gives directions for future research techniques. Practitioners in the following disciplines will find this manual very beneficial: water resources, environmental, geotechnical, and agricultural engineering."--BOOK JACKET.